Why do consumers use Facebook brand pages? A case study of a leading fast-food brand fan page in Egypt. Issue 3 (3rd July 2019) - Rasheed Gaber, Hazem; Elsamadicy, Ahmed Mousa; Wright, Len Tiu
ABSTRACT: This paper identifies the reasons that make consumers actively engage on Facebook brand pages. By adopting the Uses and Gratification Theory, this article presents a number of uses for these online brand communities. A qualitative study was conducted to collect data from the Facebook page of a leading fast-food brand in Egypt. A content analysis for the comments that were posted by consumers on the brand page over the period of three months was conducted. The findings showed that consumers actively contribute to the content of the brand page for eight reasons which are: search for information, complaining, socializing, obtaining incentives, entertainment seeking, expression of emotions, brand advocacy and enhancing social image. Prior research has focused on consumer participation in offline brand communities. Given the rapid adoption of social media based brand communities in marketing, this article expands the research focus to the social media domains, which have largely replaced traditional marketing methods. The article provides some useful guidelines for companies to follow when adopting marketing on Facebook brand pages. By understanding why consumers use these pages, companies can execute more effective social media marketing strategies that allow them to fully grasp the potentials of these new media.